Chemistry : the central science - Brown, Theodore L. (Theodore Lawrence), 1928-; LeMay, H. Eugene (Harold Eugene), 1940-; Bursten, Bruce Edward; Murphy, Catherine J. (Catherine Jones); Woodward, Patrick M.; Stoltzfus, Matthew (2015)
"Unrivaled problems, notable scientific accuracy and currency, and remarkable clarity have made Chemistry: The Central Science the leading general chemistry text for more than a decade. Trusted, innovative, and calibrated, the text increases conceptual understanding and student success in general chemistry by building on the expertise of the dynamic author team of leading researchers and award-winning professors."
Introduction : matter and measurement -- Atoms, molecules, and ions -- Chemical reactions and reaction stoichiometry -- Reactions in aqueous solution -- Thermochemistry -- Electronic structure of atoms -- Periodic properties of the elements -- Basic concepts of chemical bonding -- Molecular geometry and bonding theories -- Gases -- Liquids and intermolecular forces -- Solids and modern materials -- Properties of solutions -- Chemical kinetics -- Chemical equilibrium -- Acid-base equilibria -- Additional aspects of aqueous equilibria -- Chemistry of the environment -- Chemical thermodynamics -- Electrochemistry -- Nuclear chemistry -- Chemistry of the nonmetals -- Transition metals and coordination chemistry -- The chemistry of life : organic and biological chemistry
Includes index
Keywords: Chemistry -- Textbooks; Chemistry; Chemistry; Textbooks